Can we make sense of takotsubo cardiomyopathy? An update on pathogenesis, diagnosis and natural history. (February 2012) - Neil, Chistopher J; Nguyen, Thanh H; Sverdlov, Aaron L; Chirkov, Yuliy Y; Chong, Cher-Rin; Stansborough, Jeanette; Beltrame, John F; Kucia, Angela M; Zeitz, Christopher J; Frenneaux, Michael P; Horowitz, John D
Takotsubo cardiomyopathy (TTC) is a form of reversible acute cardiac dysfunction of uncertain pathogenesis, which occurs predominantly in postmenopausal women, often with antecedent severe stress. Systolic dysfunction most commonly affects the apex of the left ventricle. There is considerable uncertainty regarding the pathogenesis of TTC and the optimal diagnostic methodology. Acute catecholamine release may play a component role, but the regional hypokinesis is associated with an acute inflammatory process, with resultant early release of brain natriuretic peptide (BNP) and N-terminal pro-BNP. As the diagnosis of TTC has largely been a process of exclusion, there has been considerable underdiagnosis. The combination of demographics, preceding history, ECG appearances and N-terminal pro-BNP elevation may provide the basis for improved early diagnosis. Complete recovery takes at least several months, with a risk of recurrent episodes. Efforts to delineate pathogenesis, expedite diagnosis and evaluate residual disability may assist in the development of appropriate treatment regimens.